Intravitreous aflibercept or vitrectomy for initial treatment of diabetic vitreous hemorrhage? A Systematic Review of Current Evidence: Poster Presentation - Observational Study - General practitioner - Ningrum, Indra Utami Mutiara; Primarhyani, Marchia (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objectives : To assess the efficacy and safety of intravitreous aflibercept versus vitrectomy in patients with diabetic vitreous hemorrhage (VH) Methods : Cochrane Central Register of Controlled Trials, MEDLINE, and EMBASE database were searched. No constraints based on language or publication date were applied. Only randomized controlled trials (RCTs) comparing intravitreal aflibercept injection with vitrectomy procedure were included. Search results were screened independently by two authors. Data extraction and synthesis were performed according to The Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. The primary outcome measures were best-corrected visual acuity obtained at least 6 months following interventions, rate of recurrent hemorrhage, and periprocedural ocular adverse events. The quality of evidence was assessed using the GRADE tools. Results : Two clinical trials that randomized 239 eyes were included in this review. There was no evidence ofa difference in primary outcome of mean visual acuity at six months between randomized groups. However, patients receiving intravitreous aflibercept were more likely to experience recurrent VH than those undergoing vitrectomy (RR 3.12 95% CI 1.95 - 4.99, absolute effect of 32 more people with recurrent VH per 100 people treated with aflibercept). Rates of periprocedural ocular complications were similar in both groups. Conclusion : Intravitreous aflibercept safety and efficacy appear to be non-inferior compared to vitrectomy for initial management of diabetic VH. Further well-designed studies are needed to investigate the long- term effects of treatments.